One step Narylation of amines catalyzed by a non-toxic copper complex - Hashem, MA; Sultana, A; Mahmud, TB (Bangladesh Journal of Scientific and Industrial Research, 2017)
A new, simple and efficient copper catalyzed method has been developed by using a non-toxic copper complex for the preparation of amine derivatives, some of which are biologically active and literary known with high purity. The protocol to prepare the copper complex uses N-salicylidene-N-phenyl amine as the ligand with Cu2Br2 in methanol. Bangladesh J. Sci. Ind. Res. 52(1), 53-60, 2017